DOP50 Oral α4β7 integrin inhibitor MORF-057 demonstrates exposure driven biomarker response in non-human primates. (21st January 2022) - Wong, J; Lee, D; Mangada, M; Yadav, V; Troast, D; Zhong, C; Hahn, K; Wang, W; Ge, X; Sun, L; Jiang, S; Wang, B; et al.
Abstract: Background: Disruption of immune cell trafficking via integrins is a proven and effective mechanism for treating inflammatory bowel disease. When α4β7 integrin is inhibited through pharmacological intervention, immune cells destined for the gut tissue become sequestered in blood circulation and these alterations can be detected through several methods. MORF-057 is a novel, oral, selective, small molecule inhibitor of α4β7 integrin developed for treating IBD. MORF-057 demonstrated favorable tolerability, pharmacokinetic and pharmacodynamic profiles including saturating receptor occupancy and corresponding evidence for proof of biology based on effects on circulating cells during a Phase 1 clinical trial in healthy volunteers (Ray, ECCO 2021). Here we demonstrate an exposure:response relationship of α4β7 related biomarkers examined among MORF-057 treated non-human primates (NHPs) as a means for pre-clinical testing of inhibitors of this pathway. Methods: Single-cell RNA sequencing (scRNAseq) was performed on NHP CD45 + blood cells to determine baseline populations potentially impacted through exposure to MORF-057. 40 Naïve cynomolgus monkeys were enrolled over 5 separate studies and dosed orally BID with MORF-057 over 2–7 days using several dose levels to examine biomarker dynamics over a wide range of exposures. Peripheral blood was sampled at various timepoints (n= 125) and assayed using: mass spectroscopy, flow cytometry (FACS), and mRNA quantification to determine MORF-057 exposure levels, on-target receptor occupancy (RO), immune cell subset changes, and CCR9 mRNA levels. Results: MORF-057 Ctrough ranged from 3.3–429 ng/ml. In samples tested for RO, MORF-057 achieved >95% saturation of α4β7 even with the lowest Ctrough of 4.5 ng/ml. MORF-057 treatment led to significantly sustained increases in circulating β7high CD4 + T memory cells detectable as early as 24h post-exposure. A maximal effect where β7high cells accounted for approximately 60% of the T memory population was achieved at saturating receptor occupancy (Fig., left). CCR9 mRNA values demonstrated increases upon drug exposure (Fig., right). Conclusion: In NHP, acute changes in circulating β7high T memory cells was a sensitive biomarker demonstrating a dose-dependent response to MORF-057 exposure. CCR9 mRNA levels also showed similar exposure related changes reflecting its expression on a subset of β7high cell types. Analysis of scRNAseq shows expression of α4β7 on other cell types beyond T memory cells including: NK, NKT, B cells, plasmablasts, monocytes, and eosinophils. Pharmacodynamic changes in NHP are consistent with human Phase 1 data in healthy volunteers.